Validation of an alignment method using motion tracking system for in-vitro orientation of cadaveric hip joints with reduced set of anatomical landmarks. (January 2018) - Bsat, Suzan; Haider, Ifaz; Speirs, Andrew; Beaulé, Paul; Frei, Hanspeter
Highlights: Orienting cadaveric hip joints with limited anatomical landmarks in-vitro using guided axes resulted in errors of ±8° and ±12° in at least one of three orientation angles used to place the femur and pelvis in the neutral position, respectively. Orienting cadaveric hip joints with limited anatomical landmarks in-vitro by visual approximation resulted in errors of ±10° and ±15° in at least one of three orientation angles used to place the femur and pelvis in the neutral position, respectively. The newly developed alignment method for orienting cadaveric hip joints with limited anatomical landmarks in-vitro resulted in orientation angles achieved to within one degree with standard deviation of ±0.58°. Using FEM fracture loads were calculated for each femur oriented using guided axes and visual approximation (naked eye). In most cases, the largest error in fracture load among all trials exceeded 30%, relative to a femur oriented without any error in the orientation angles. Abstract: Accurate in-vitro orientation of cadaveric hip joints is challenging due to limited available anatomical landmarks. Published hip joint in-vitro investigations commonly lack details on methods used to achieve reported orientations and the accuracy with which the desired orientation has been achieved. The aim of this study was to develop an accurate method for orienting hip joints with limited anatomical landmarks for in-vitro investigations, and to compare this method against orientation using guiding axes and by visual approximation. The proposed orientation method resulted in orientation angles achieved to within one degree (SD ± 0.58°). For most specimens, orientation using physical tools resulted in errors of ±8° and ±12° in at least one of three orientation angles used to place the femur and pelvis in neutral orientation, respectively. Precision was also worse, with SDs ranging from ±1° to ±5° for orientation angles of femoral specimens and SDs ranging from ±1° to ±8° for pelvic specimens. The error in the orientation angles was worse for orientation by visual approximation and the range of SDs were greater for both the femur and pelvis. Finite element modeling was used to assess the effects of observed orientation errors, on prediction of fracture load. In most cases, the largest error in fracture load among all trials exceeded 30%, relative to a femur oriented without any error in the orientation angles.